Use of free uroflowmetry vs pressure-flow studies in the diagnosis of overactive bladder syndrome in females. (December 2016) - Nowakowski, Ł.; Futyma, K.; Ziętek, A.; Bogusiewicz, M.; Gałczyński, K.; Rechberger, T.
Abstract: Objectives: To determine if pressure-flow study (PFS) parameters, including flow index (FI) calculated by dividing average urethral flow by maximal urethral flow, increase the accuracy of urodynamic studies in the diagnosis of overactive bladder (OAB). Study design: Retrospective study to evaluate the medical history and urodynamic examination results of female patients diagnosed with lower urinary tract symptoms (LUTS) between January 2014 and December 2015. Patients were stratified into four groups depending on the type of LUTS: OAB; stress urinary incontinence (SUI); mixed urinary incontinence with predominant SUI symptoms (MUI-SUI); and mixed urinary incontinence with predominant OAB symptoms (MUI-OAB). Results: OAB was diagnosed in 26 (15%) patients, SUI was diagnosed in 93 (52%) patients, MUI-OAB was diagnosed in 43 (24%) patients, and MUI-SUI was diagnosed in 17 (9%) patients. FI calculated using free uroflowmetry (FI-free) was significantly lower in the OAB group compared with the other groups ( p  < 0.01). Analysis revealed no difference in FI-free between the SUI, MUI-SUI and MUI-OAB groups. Significant differences were found between the study groups for most free uroflowmetric parameters, including maximal urethral flow, average urethral flow and micturition volume ( p  < 0.05). Similar differences were not found in PFS parameters. Conclusions: The decrease in the urethral lumen due to the presence of a transurethral catheter in patients with OAB, in contrast to women with SUI and MUI, was not found to influence FI calculated using free uroflowmetry or PFS. FI may serve as an important objective diagnostic tool for OAB, but only when calculated from free uroflowmetry parameters when assessing patients with LUTS.